CONSUMER PREFERENCES ANALYSZE TO BUYING "GULAKU" BRAND of SUGAR PRODUCTS IN YOGYAKARTA CITY - Farhiyatul Islamiyah; Danang Manumono; Ari Astuti (JURNAL ILMIAH AGRITAS, 2019)
The development of the branded sugar industry in Indonesia is increasing every year. This makes consumers faced with a variety of alternatives that exist so that consumers tend to have certain preferences before making a purchase process for the product. Consumer characteristics and preferences are important things that the company must know in order to be able to compete with other companies. The purpose of this study is to find out the characteristics of consumers and analyze the factors that influence consumer preferences in buying Gulaku brand sugar products in the city of Yogyakarta. The research method used descriptive quantitative method, the sampling technique in the form of accidental random sampling with the number of respondents as many as 70 people. The results of this study are: (1) Consumers who buy Gulaku brand sugar in Yogyakarta City are dominated by female consumers, aged 20-25 years, married and working as private employees with an income of Rp. 1,000,000.00; -Rp. 2,000,000.00 / month. (2) Variables Culture, personal, brand image and promotion have a significant influence on consumer preferences in buying Gulaku brand sugar products in Yogyakarta City. (3) Price and product packaging variables have no significant effect on consumer preferences in buying Gulaku brand sugar products in Yogyakarta City.